Основы политики США в Черноморском регионе в контексте взаимодействия Российской Федерации и Турецкой Республики - Бебешко, Е.В. (Культура народов Причерноморья, 2014)
Настоящая статья посвящена выявлению основ внешней политики США в Черноморском регионе в свете взаимодействия России и Турции в 1991–2014 гг. Для достижения поставленной цели анализируются внешнеполитические документы США, а также позиции различных авторов по проблемам, обозначенным в регионе. Анализ принципов формирования и реализации американских внешнеполитических концепций в Черноморском регионе, нацеленных на потерю геополитической субъектности России и Турции, дают основания ожидать сближения этих стран и серьезного пересмотра региональных приоритетов США и их политики в Черноморском регионе. Ця стаття присвячена виявленню засад зовнішньої політики США у Чорноморському регіоні в контексті взаємодії Росії та Туреччини в 1991-2014 рр. Для досягнення поставленої мети аналізуються зовнішньополітичні документи США, а також позиції різних авторів із проблем, позначених в регіоні. Аналіз принципів формування та реалізації американських зовнішньополітичних концепцій в Чорноморському регіоні, націлених на втрату геополітичної суб'єктності Росії та Туреччини, дають підстави очікувати зближення цих країн і серйозного перегляду регіональних пріоритетів США та їх політики в Чорноморському регіоні. The article is devoted to revealing the foundations of American foreign policy in the Black Sea region in the context of interaction between Russia and Turkey in 1991–2014. To achieve this goal, the United States foreign policy documents were examined, as well as positions of various authors on the problems identified in the region. It was stated, that Black Sea region has been the object of American policy in connection with the pursuit of control over Eurasia after the collapse of the USSR and the formation of independent states. The concept of the United States’ course in the 1990s contained maintaining geopolitical pluralism and the promotion of democracy in the former Soviet republics, the creation of the Euro-Atlantic security system with the NATO as its core; inclusion of Russia as a "junior partner" in it; formation of different unions. To achieve this goal, the tasks were set to develop regional cooperation, increase investment in energy infrastructure, reform energy sector of the states in accordance with Western standards, etc. Change in the situation in the early 2000s led to the formation of the American concept of "Greater Black Sea region" on the basis of interaction of the United States and the EU with the countries in the region and increasing the role of some states, particularly Turkey. But this project was strongly opposed by Russia. The analysis shows that problems, encountered in the process of formation of the Greater Black Sea region, caused the United States to shift implementation of its policies from regional to the country basis. America's primary interest is to provide a situation in which no one power would control this geopolitical region. In this context, the main aim of American policy toward Russia and Turkey in the Black Sea region appears to be triune geopolitical problem: avoiding the Russian-Turkish rapprochement, simulations of mutual deterrence of these two states, keeping for itself the role of arbiter, reinforcing its position in the region, both by maintaining Turkey in Euro-Atlantic structures and strengthening relations and influencing the policies of other countries in the region. Recently, however, US-Turkish relations soured considerably, as Turkey is moving away from the United States and the EU, willing to become an independent pole of the emerging multipolar world. So the analysis of principles of formation and realization of American regional course gives the opportunity to make prognosis in the context of tightening relations between the USA and Russia, in connection with the events in Ukraine in 2014 and the total transformation of the international political system, that rapprochement between Russia and Turkey should be expected, as well as a serious revision of the regional priorities of the United States and its policy in the Black Sea region.